EKSISTENSI PERNIKAHAN PEREMPUAN SAYYID DI DESA CIKOANG KABUPATEN TAKALAR - Edi Hariyadi; Firdaus W Suhaeb (Universitas Negeri Makassar, 2021)
Sayyid marriages that occur in the community of Cikoang Village, Takalar Regency are one of the distinguishing characteristics for ordinary people in carrying out their marriages, namely there are separate rules for sayyid women, namely Sayyid women cannot marry men who are not of Sayyid descent or descent of the Prophet Muhammad SAW. The research approach used descriptive qualitative methods carried out in Cikoang Village, Takalar District. Primary data obtained by means of observation, interviews, documentation. Secondary data comes from books and journals. This research shows that the way to preserve marriage still exists today, namely, the factor of belief, they believe that their descendants come from the descendants of the Prophet Muhammad. And the rule factor is that sayyid circles have rules in carrying out marriage, namely sayyid women cannot marry men who are not of Sayyid descent, but sayyid men can marry women outside their circle. and the witness factor, namely for women who violate these rules will be subject to sanctions in the form of no longer being considered in their family and among their circle as Sayyid descendants and are considered dead. Meanwhile, the solution for Sayyid women who do not have a partner among them is to match a Sayyid male. And the second solution is to allow Sayyid women to marry under the applicable sanctions.